Proceedings of the 7th International Conference on Entrepreneurship and Business Management 2018
DOI: 10.5220/0008487800380043
|View full text |Cite
|
Sign up to set email alerts
|

Culinary Experience of International Tourists in Indonesia: A Study on Denpasar and Yogyakarta Tourist Destinations

Abstract: Culinary tourism offers tourists to learn new cultures through their experiences with local food of the visited destinations. The literature shows that although the concept of experience quality, tourist satisfaction in the context of culinary tourism has been confirmed in many previous studies, a study that examines the linkages between those variables and destination experience specifically the culinary experience with local Indonesian food is still rare. The aim of this study was to investigate the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…That is, food quality appeared to be the main satisfier indicator of culinary experience satisfaction (CES1) [22]. However, this finding is in contrast with the previous study done to the international tourists in Denpasar and Yogyakarta in which it was found that their satisfaction with the culinary experience was mainly determined by the dining place quality instead of the food quality [21].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…That is, food quality appeared to be the main satisfier indicator of culinary experience satisfaction (CES1) [22]. However, this finding is in contrast with the previous study done to the international tourists in Denpasar and Yogyakarta in which it was found that their satisfaction with the culinary experience was mainly determined by the dining place quality instead of the food quality [21].…”
Section: Discussioncontrasting
confidence: 65%
“…This finding is also in line with the previous study measuring the culinary experience quality of international tourists in Denpasar and Yogyakarta. It was found in the study that culinary experience quality was constructed mainly by ambience of the dining place, unique food presentation and local people's hospitality [21].…”
Section: Discussionmentioning
confidence: 99%
“…The development of gastronomic tourism contributes to integrating traditional primary productive functions with the specialized tertiary functions, increasing the sources of income and improving the income and employment levels of the local population and facilitating the multifunctionality of rural territories. However, it also favours cities; when gastronomy becomes an element that is part of the cultural of a city, tourists are inspired to make gastronomic journeys outside of the context of gastronomy festivals [19,20]; rather, they desire an experience that provides heritage cooking [21], a hedonistic perspective [22], an opportunity to learn new dishes [23], a discovery of different culinary experiences [24] or the opportunity to eat at a restaurant included in a prestigious guide [25].…”
Section: Plos Onementioning
confidence: 99%
“…According to Sunuantri, Hanita, & Rahayunianto (2019), culture is mainly shaped and learned, it consists of a social pattern of a human life that portrays an intricate, abridge, and comprehensive. Culture has been the part of tourism, and through culture, gastronomy tourism is brought to become the part of cultural tourism because of its possibility to learn new and fascinating smells, flavors, and tastes of the local culture (C. Widjaja, Wijaya, Jokom, & Kristanti, 2019).…”
Section: Culturementioning
confidence: 99%